1994
DOI: 10.1139/z94-147
|View full text |Cite
|
Sign up to set email alerts
|

Methods of scent marking in the domestic cat

Abstract: Carnivores use various scent-marking methods. Semi-feral domestic cats (Felis silvestris catus) were observed to use the same means as their wild counterparts. Adult males performed most urine spray marking. Cats scratched tree bark, producing a visual mark, and probably used trees both as markers and for claw sharpening. Most scratching trees were located along frequently used paths rather than along territorial boundaries or scattered randomly throughout a home range. Bark consistency affected the tree speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 13 publications
2
90
0
10
Order By: Relevance
“…It is also possible that rubbing has all of these functions at different proximate and ultimate levels (Tinbergen, 1963). Some authors have noted a distinction between scent marking rub and social rub (Johnson, 1973;Peters and Mech, 1975;Feldman, 1994;Bel et al, 1995;Blumstein and Henderson, 1996;Weiss et al, 2015). However, given the experimental setup of this study, social rub (also called bunting or allorubbing) is a more appropriate contextualization of the behaviour, since it was focused on the human-cat interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that rubbing has all of these functions at different proximate and ultimate levels (Tinbergen, 1963). Some authors have noted a distinction between scent marking rub and social rub (Johnson, 1973;Peters and Mech, 1975;Feldman, 1994;Bel et al, 1995;Blumstein and Henderson, 1996;Weiss et al, 2015). However, given the experimental setup of this study, social rub (also called bunting or allorubbing) is a more appropriate contextualization of the behaviour, since it was focused on the human-cat interaction.…”
Section: Discussionmentioning
confidence: 99%
“…cattle, Boivin et al, 1998;rats, Davis et al, 1997). Furthermore, while Soennichsen and Chamove (2002) randomised the order of body areas touched, examination of feline rubbing has revealed that cats rub against objects and other individuals in a set order starting at the head and facial region and, in the case of allo-rubbing, often finishing at the tail (Feldman, 1994;Crowell-Davies, 2003). It is unknown whether such an order is important in human-cat interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, olfaction appears to play an important role from birth, being especially important in the early days of the mother-kitten relationship (Ewer 1959;Mermet et al 2007;Raihani et al 2009;Arteaga et al 2013). Olfactory cues remain important throughout a cat's life, providing social information about conspecifics (Verberne and de Boer 1976;Verberne 1976;Natoli 1985), defining home ranges (Feldman 1994), and influencing the human-cat relationship (Pageat and Gaultier 2003;Ellis and Wells 2010;Mills et al 2011). Auditory and visual developments progress more slowly.…”
Section: Perceptionmentioning
confidence: 99%